2016
DOI: 10.3126/nepjoph.v8i1.16155
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome and early complications of sutureless and glueless scleral fixated intraocular lens

Abstract: Introduction: In the absence of capsular support, anterior chamber intraocular lens (IOL), iris fixated IOL and sutured scleral fixated intraocular lens (SFIOL) implantation have been performed for many years. Recently sutureless glued SFIOL have been used as a primary or secondary procedure to correct aphakia. In this study we have used sutureless and glueless technique of SFIOL implantation. Methodology: An interventional case series was conducted. Aphakic patients without capsular support, sub-luxated lens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Most authors have reported a low IOP in their cases following surgery in the immediate postoperative period. 21 , 24 In our study, postoperative hypotony was not present in any of the cases. Instead, raised IOP was the most common immediate postoperative complication seen in 4 (4.5%) of the cases.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Most authors have reported a low IOP in their cases following surgery in the immediate postoperative period. 21 , 24 In our study, postoperative hypotony was not present in any of the cases. Instead, raised IOP was the most common immediate postoperative complication seen in 4 (4.5%) of the cases.…”
Section: Discussionsupporting
confidence: 41%
“…The results of our technique have been encouraging, with 94% of the cases attaining a stable BCVA of 6/12 or better at 6 weeks. Agarwal et al 21 have reported 72% of their patients undergoing SFIOL of having vision better than or equal to 6/18 in a similar setup but with a different technique. They have also reported that there was no drop in BCVA at 1-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of corneal edema after SF IOL implantation has been reported to range from 1% to 41%, with most of the studies reporting this in the early postoperative period (∼1 month). 12,13,17–20,23,25,28,30,31,40,44,49 After RP-IC IOL implantation, Hazar et al and Shanida et al reported transient corneal edema as an early postoperative complication in 4.1% and 30% of eyes, respectively, which resolved after 1 week. 23,36 In addition, Faria et al reported corneal edema in 2.85% of eyes (3/105) over a mean follow-up of 23 months.…”
Section: Resultsmentioning
confidence: 99%
“…16–18,25,39,40,44,49,63–65,77 Among SF IOL studies, Leung et al and McKee et al reported broken haptic in 6.3% and 2% of cases after 1 and 3 months, respectively; Agarwal et al reported dislocated haptic in 1.6% of cases after a mean follow-up of 8.1 months. 28,88,89 Chan et al reported vitreous incarceration at the wound site in 1.4% of eyes after sutured SF IOL, and Sy Oh et al reported 8.3% after sutureless SF IOL implantation. Yalniz-Akkaya et al reported wound leakage in 3.4% of eyes, which required resuturing within 1 month.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, this complication was more frequent than hypertension with haptic-fixation techniques. 9 , 39 Kam et al 38 reported early ocular hypertension and vitreous hemorrhage to be more frequent following SFIOL implantation without concurrent PPV. In our series, all patients were vitrectomized, which explains the lower rate of vitreous hemorrhage.…”
Section: Discussionmentioning
confidence: 99%